2021
DOI: 10.1186/s13046-021-01882-1
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic lncRNA ZNF561-AS1 is essential for colorectal cancer proliferation and survival through regulation of miR-26a-3p/miR-128-5p-SRSF6 axis

Abstract: Background Long non-coding RNAs (lncRNA) are reported to influence colorectal cancer (CRC) progression. Currently, the functions of the lncRNA ZNF561 antisense RNA 1 (ZNF561-AS1) in CRC are unknown. Methods ZNF561-AS1 and SRSF6 expression in CRC patient samples and CRC cell lines was evaluated through TCGA database analysis, western blot along with real-time PCR. SRSF6 expression in CRC cells was also examined upon ZNF561-AS1 depletion or overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…LncRNA is a type of RNA that is longer than 200 nucleotides and lacks protein-coding ability (6). Nevertheless, lncRNAs still play an extremely broad role in important life activities of organisms, including epigenetic modification of genes, splicing and editing of RNA, regulation of miRNA, and folding of protein molecules (7,8). Aberrant expression of lncRNAs has been observed in human cancers, where they can act as either tumor suppressor genes or oncogenes, depending on the environment in which tumor cells are located (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA is a type of RNA that is longer than 200 nucleotides and lacks protein-coding ability (6). Nevertheless, lncRNAs still play an extremely broad role in important life activities of organisms, including epigenetic modification of genes, splicing and editing of RNA, regulation of miRNA, and folding of protein molecules (7,8). Aberrant expression of lncRNAs has been observed in human cancers, where they can act as either tumor suppressor genes or oncogenes, depending on the environment in which tumor cells are located (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-128-5p participated in the progression of colorectal cancer (Si et al, 2021). Our study revealed that these miRNAs and lncRNAs were related to the prognosis of sarcoma patients.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, SRSF6 overexpression is significantly associated with poor overall survival (Wan et al, 2019). Park et al showed that SRSF6 protein was overexpressed in a cohort of colorectal patients by Western blot (Park et al, 2016), which was further confirmed in another study by Western blot (Si et al, 2021). However, Lin et al showed that SRSF6 protein was downregulated in colorectal cancer tissues in eight patients compared with adjacent normal tissues by Western blot (Lin et al, 2017).…”
Section: Colon and Colorectal Cancermentioning
confidence: 95%
“…circFBXL5 functions as a ceRNA to sponge miR-660 and upregulate SRSF6 expression in breast cancer ( Zhou et al, 2020a ). Another example is that lncRNA ZNF561-AS1 can sponge miR-26a-3p and miR-128-5p to upregulate SRSF6 expression in colorectal cancer ( Si et al, 2021 ).…”
Section: Regulatory Mechanisms Of Serine/arginine-rich Splicing Factor 6 Expression and Functionmentioning
confidence: 99%